Code smells survival analysis in web apps - Rio, A. (2019)
Web applications are heterogeneous, both in their target platform (split across client and server sides) and on the formalisms they are built with, usually a mixture of programming and formatting languages. This heterogeneity is perhaps an explanation why software evolution of web applications (apps) is a poorly addressed topic in the literature. In this paper we focus on web apps built with PHP, the most widely used server-side programming language. We analyzed the evolution of 6 code smells in 4 web applications, using the survival analysis technique. Since code smells are symptoms of poor design, it is relevant to study their survival, that is, how long did it take from their introduction to their removal. It is obviously desirable to minimize their survival. In our analysis we split code smells in two categories: scattered smells and localized smells, since we expect the former to be more harmful than the latter. Our results provide some evidence that the survival of PHP code smells depends on their spreadness. We have also analyzed whether the survival curve varies in the long term, for the same web application. Due to the increasing awareness on the potential harm-fulness of code smells, we expected to observe a reduction in the survival rate in the long term. The results show that there is indeed a change, for all applications except one, which lead us to consider that other factors should be analyzed in the future, to explain the phenomenon.